8 - Youth Religiosity and Moral Critique: God, Government and Generations in a Time of AIDS in Uganda - Christiansen, Catrine (Africa Development, 2021)
This article stresses the centrality of youth questions in Uganda, whereby HIV, religious and political issues are contributing to changes in the societal landscape. The ‘youth question’ has become a very important focus in developmental aids, but its conceptualization still remains ambiguous. It is this ambiguity in the conceptualization of young people, as victims and agents, which informs efforts to involve youth in the work towards preventing the spread of HIV and mitigating the nega- tive impact of AIDS. The article demonstrates that young people largely consent to the lower social positioning of youth as they regard them- selves as persons still in the making, and they find this positioning a comfortable zone from which to criticise the older generations for not maintaining family solidarity and providing sufficiently for the younger generation. Based on a drama developed by a Catholic youth group, it shows how youth combine cultural values, child rights and Christian morality to present the selfishness and low morals of the older genera- tions, and themselves, as keepers of morality in the interest of the soci- ety as a whole. Drawing on the human rights framework, development agencies refer to young people’s rights to partake in matters regarding their own lives and entitlement, to grow up in safe spaces of socialization and develop skill. The concept used in this article tends to define ‘youth’ as a category of social being and social becoming where sexuality is becoming part of political discourse.